THE IMPLEMENTATION OF POP SONG TO TEACH WRITING NARRATIVE TEXT TO THE ELEVENTH GRADERS OF SMAN 17 SURABAYA (RETAIN, 2014)
THE IMPLEMENTATION OF POP SONG TO TEACH WRITING NARRATIVE TEXT TO THE ELEVENTH GRADERS OF SMAN 17 SURABAYA Trisiyana Agustilawati Pendidikan Bahasa Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Surabaya trisiyana24@gmail.com Him’mawan Adi Nugroho, S.Pd., M.Pd. Pendidikan Bahasa Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Surabaya Himmawan_95@yahoo.co.id Abstrak Menulis adalah salah satu ketrampilan yang harus dipelajari oleh para siswa dalam mempelajari bahasa Inggris sebagai bahasa asing. Dan menulis bukanlah hal yang mudah hanya dengan menyusun kata-kata. Terkadang siswa mengalami kesulitan dalam menyusun kalimat naratif, seperti mencari arti kata, mencari ide, dan mencari kata-kata. Lagu adalah sumber ymedia yang paling mudah yang dapat dilakukan di dalam kelas. Seperti yang dikatakan oleh Lo and Fai Li (1998:8), belajar bahasa Inggris melalui lagu juga menyediakan atmosfir yang bagus untuk siswa, yang biasanya tensesnya ketika berbicara bahasa Inggris dalam kelas formal. Dan kasusu ini diadakan pada kelas XI di SMAN 17 Surabaya, karena siswa yang berumur 17 tahun suka mendengarkan musik. Penelitian ini menggunakan deskriptif kualitatif. Penelitian ini bertujuan untuk menjelaskan penerapan lagu dalam pembelajaran menulis naratif pada kelas XI melalui penggunanan lagu. Peneliti menggunakan daftar cek observasi dan tugas-tugas siswa sebagai alat penlitiannya. Data diperoleh dari observasi selama penerapan lagu dalam pembelajaran naratifdan tugas siswa pada pertemuan pertama dan pertemuan kedua. Setelah melakukan observasi yang diadakan di SMAN 17 Surabaya, peneliti menjelaskan dua penemuan. Pertama, penerapan lagu untuk mengajar [elajaran naratif pada kelas XI berjalan dengan baik. Dan kedua, peneliti menemukan bahwa dengan lagu kemampuan siswa dalam menulis semakin baik dalam setiap pertemuan. Kesimpulan dari semua ini adalah dengan menggunakan lagu siswa dapat menulis cerita naratif dengan mudah. Dan hasil tugas siswa sangat memuaskan, dan hasilnya dapat dilihat dari hasil tugas siswa setiap pertemuannya. Kata Kunci: menulis, lagu, teks naratif Abstract Writing is one of the skills which should be learned by students in learning English as a foreign language. And writing is not simply a matter of putting words together. Sometimes the students have difficulties in composing narrative writing, such as: stuck to get diction, getting idea, and ordering the words.Songs are one of the most enchanting and culturally rich resources that can easily be used in language classrooms. As stated by Lo and Fai Li (1998:8), learning English through songs also provides a non-threatening atmosphere for students, who usually are tense when speaking English in a formal classroom setting. And this study conducted on the eleventh graders, because the students in 17 years old love listening music.This research was designed based on descriptive qualitative research. It aims to describe the implementation of song to teach writing narrative text to the eleventh graders of SMAN 17 Surabaya and to describe the result of the students’ writing narrative text of SMAN 17 Surabaya toward the implementation of song. The researcher uses observation checklist and students’ writing task as the instrument. The data are obtained from the observation during the implementation of song in teaching narrative text and the students’ writing narrative task in the first meeting and second meeting.After conducting the observation which is held in SMAN 17 Surabaya, the researcher described two findings. The first finding showed that the implementation of song to teach writing narrative text to the eleventh graders of SMA Negeri 17 Surabaya did well. Then, the second finding showed by using a song, the students’ writing ability was getting better in every meeting.In conclusion, by using a song the students can write narrative text easily and the result of students’ work was satisfaction, it can be seen from the student’s task in every meeting. Keywords:Writing, song, narrative text INTRODUCTION In Indonesian, education of English is one of important subjects. But studying English is not easy for many Indonesian students since it is a foreign language. Foreign language is the language that is being learned not spoken in the local community (Robert, 1998: 4). The students must have good communication in both oral and written form. Oral form is that speaking and listening, and written form is that writing in reading. Writing is not simply a matter of putting words together. It is a recursive process. It is a process of revision and rewriting. And writing is not the only activity of producing words into paragraph or essay but there are also many aspects include in it (Nunan, 2003). Writing is a process repeated, namely process of revising and rewriting. The students must know some strategies in composing narrative writing such as: making outline, using picture, using dictionary, sharing with friends, using the tools (audio, audio-visual) or learning’s aids( a guide). Songs are one of the most enchanting and culturally rich resources that can easily be used in language classrooms.There are two advantages by using song in teaching English. It is supported by Murphey (1992,:3), he says that two major advantages in teaching with song are memorable and motivating. The first is memorable, song has melodies that make the words or sentences essay to remember or memorize. The second is motivating, without motivation success will be hard to come, so that the students need some motivation in learning process. When songs are used in teaching process, it is enjoyable. So, the students are more motivated to learn English. Therefore, using songs as a media in teaching writing narrative text can attract the students’ interest and motivate them in learning English. Songs carry massage along its melody that can arise the students’ interest and finally make them motivate to understandand memorize the meaning of the massage ( Hancock, 2001). Based on those reasons above, the writer conducts this study on the eleventh graders. This grade is chosen because the students have problems in composing narrative text. The students in 17 years old have a habit listens a song in their mp3, radio, or television. When they have a problem in their love story, they show by listening music. So, the writer hopes by using song the students have ability in writing a narrative text. The writer finds several previous studies which are related to the writer’s study. The first thesis title is “Using Songs as a Suplementary Material to Teach English Skilltoward Senior High School Students” written Rahayu Yulianti (2000). In her thesis, she used experimental research for her reseach design and she focused in listening skill. She found that songs could be used as a suplementary material for improving students’ ability in listening skill. The next thesis entitled “Using Song to Teach English Vocabulary to Kindergarten” written by Enny Soebagiarsih (2002). She used qualitative research for her research design. She found that the use of song to teach English vocabulary as an alternative and an effective way to improve vocabulary mastery of the students. RESEARCH METHODOLOGY The research methodology is used to describe how the researcher found the result of this study. The research methodology discusses the research design,subject of the study, setting of the study, data of the study, research instrument, data collection technique, and data analysis. This research was designed based on descriptive qualitative research. It described the implementation ofpop song to teach writing narrative text to the eleventh graders of SMAN 17 Surabaya. The data were analyzed and described by the researcher in the form of words, phrases, or sentences. The purpose of this study was to describe how the teacher uses pop song in teaching writing narrative text and to know the students’ writing ability toward the implementation ofpop song to teach writing narrative text to the eleventh graders. The subject of the study was XI IPA 4 at SMAN 17 Surabaya. It was located in Jl. Rungkut Asri Tengah no 2. This research was conducted in the classroom Furthermore, the classroom was provided by facilities which support the learning activivities, such as LCD, Computer, and sound. The researcher used observation checklistand students’writing task in order to collect the data. These data were expected to answer the question in the statement of the problems.The result of observation checklist was used to know the process of the activities used by the teacher. It was used when the teacher was conducting the activities. The data was taken according to the fact during observation in a classroom. Then, the researcher took the students’ writing task to know the resukt of the student in making narrative text after they taughed narative text by using a song. Instrument is a tool used to collect data in order to overcome of the research (Robert Lado, 1964:71). furthermore, Arikunto (2006) describes that there are some instrument that can be used in a research, those are problems sheet, questionnaire, interview guideline, and checklist. The instruments were used by the writer to get the data were observation checklist andstudents’ writing task.The observation checklist contained the steps that the teacher and the students had to do in the teaching learning process. And the students’ task would be given depend on the activity, in this case, there were two tasks. The writer would use words in scoring students’ writing result (very good, good, fair, and poor). The researcher took a part as an observer. The data of observation checklist was collected when the teacher did her activity in the class. It was taken when the teacher implemented the pop songto teach writing narrative text. Then, the data of students’ writing task weretaken after the students finished their writing narrative. The whole data which came from observation checklist and students’ writing task would be analyzed and described in form of words or description.The researcher wouldanalyze everything she saw, thought, and experienced in the classroom. The first, the researcher would analyze the students’ writing ability after the implementation of song through students’ writing task in the last meeting. The results of the students’ writing task would be analyzed using rubric score writing which was presented in a word or description. And then, the researcher would make conclusion and interpretation. FINDING AND DISCUSSION In this part, the researcher describes the result and discussion of the observation which has been held. The result and discussion of the implementation of pop song to teach writing narrative text to the eleventh graders of SMAN 17 Surabaya will be presented descriptively. The Finding of The First Observation The first meeting was held on Thursday, 20th March 2014. The observation took place at XI Science IV. There were 37 students in this class. The class of English lesson began at 10.00 a.m. the teacher started the class with opening session. She greeted the students. Then the teacher checked the attendence list. There was one absent. So, there were 36 was present in the class. After checking attandence list, she introduced the researcher to the students. She explained that the researcher would join the class and their teaching and learning activities would be observed in three meeting. The teacher prepared the material which used to teach narrative text. She prepared the sound, the LCD, and the laptop for teaching this lesson. While she was preparing the media, the students prepared their books and had short discussion with their friend. In pre activity, the teacher explained the goal of the teaching and learning and the activities that they were going to do that day. She told the students that that day they would learn how to write narrative text using a song. The teacher also said she would review narrative text, because the students had gotten that material when they were in tenth grade. The teacher asked the students to open their English book. The teacher gave the students an example of narrative text on the book and explained the generic structure of the story. The students were not too confused about the explanation of narrative text because they have already learned narrative text in the first class. After the teacher explained the activities that they were going to do. The teacher told them that that day they listened the song. The tittle is “A Most Peculiar Man”. The students were very happy, because it was the first time they studied while listening music. Before playing the song, the teacher gave the text which was incomplete about the lyric. She gave three minutes to read the lyric. After that, the teacher played the song three times. The teacher asked the students to pay attention during listening the song, because the students had to listen carefully to fill the blank sentences. After playing the song three times, they discussed the story of the song “A Most Peculiar Man” together and made a composition narrative text.The next step, after the students finished listening to the song, the teacher asked the students to read the lyrics of the song completely. She asked one students to read aloud about the lyric. After that, she asked them to find some vocabularies which they did not know the meaning yet. And then some students asked the meaning of peculiar, tiny, notified. After finding some difficult vocabulary and the meaning, the teacher and the students interpreted the story on the song together. After the teacher and the students discussed about the song, the teacher asked the students made a short story about narrative text. The teacher gave 40 minutes to make a narrative text. The story was up to the students. While the students were writing a narrative text, the teacher walked around the class. She checked the students’ writing and asked whether they had difficulties in making story. And some students asked about vocabulary. The class was sometimes silent and sometimes was crowded. Because they confused what story they had to write. After 40 minutes left, the teacher asked the students to submit their work. Altough some students had difficult in making narrative text, they had finished their works. The teacher would read the students’ writing and she would give feedback to their writing next meeting, because the time was end. Before ending the class, the teacher asked the difficulties that they faced. Then some of them told about their difficulty in vocabularies used, and some students told that they confused about making the story. Then, when the bell rang she reminded the students that in the next meeting they will learn a song again. And the teacher asked the students to prepare another story that they would make but it was not taken from book, newspaper or internet. Then the teacher said goodbye to the class. The Finding of The Second Observation The second observation was conducted on Tuesday, 25th March 2014. The class started at 8.15 a.m. As usual, before starting the lesson, the teacher ordered the students to clean the whiteboard and put the rubbish under their table. Then, she greeted the students and checked the attendance list. All of the students were present on the second observation. Thirty seven students joined the class.After that, the teacher reviewed a little about the material in the last meeting which was news item. The teacher asked the students some questions from the generic structure, language feature and the goal of the narrative text. All students could answer easily and they still remembered what their teacher explained in the last meeting. While giving questions, the teacher asked one of the students to help her prepare the sound system, laptop, and LCD. She explained that they would have the same activity as the previous meeting. They would listen a different song, discussed it and made a composition. After the teacher gave the instruction, the song was ready to play and the text had been given to the students, the teacher played the song. On the first meeting, the song was “A Most Peculiar Man”. And on the second meeting the song was “Abiyoyo”. That song was same as the last observation, it was easy listening. The teacher played the song again and asked the students to pay more attention and not to be noisy at all. When the song had been played for three times, the teacher asked the students to listen carefully to fill the blank in the lyric. The song had been played for three times.And than, the teacher and the students discussed what the song about. The teacher asked some students to tell what the song is. After discussing the song, then the teacher asked the students to make narrative composition. She gave 40 minutes to the students to make a story about narrative. While the students were making narrative composition, the teacher walked around the class, checked the students’ work. The students made narrative composition quickly, because they had understood about generic structure and language feature. So they worked easily. Sometimes the class was crowded, because they still did not know the vocabulary yet, and they asked each other. The teacher tried to answer the students’ question by walking around the class. The time was almost over, it was ten minutes left. The teacher asked the students to collect their writing. She said that she would correct the students’ work in teachers office.After the teacher explained what they would do on the next meeting then the teacher greeted to the class, and asked the students not to be noisy because the next teacher would come. The Finding of The Third Meeting The third observation or the last observation was conducted on Thursday 27th March 2014. The class began at 10.30 a.m. Actually, the class had to begin at 10 a.m, because there was meeting in teachers office, so the class missed 30 minutes. Just like on the two observations before, the teacher greeted the students and she asked the students condition after having a break. And she also said sorry because she came late. She asked the condition of the class included the equipment needed during the lesson and others. After all the things are complete, the teacher checked the student’s attendance list. In this meeting, there was one student absent because of sick, so the number of students were 36 students that followed the class that day. Then, she reviewed the last material that had been presented on Tuesday. After reviewing the material, then the teacher informed the students who got the best score in writing narrative text. The teacher mentioned Annur who has best score in that class. Annur read her story in front of class loudly, and all of the students listened carefully. The class was very silent, because they wanted to listen the story which get score 95. The story was great, vocabulary that she used was not difficult, so that the students understood the story. And the grammar was correct, such as the use of past tense, appropriate irreguler verb, and organized composition. After Anur read her story, the teacher asked some students to read their own writing in front of class. There were some students did want to read their writing, because they did not get confidence in their writing, so they were ashame to read their story aloud in front of their friends. The teacher gave advice to the students that they needed to be ashame, because the story was origin, it was made by they self. And they had to exercise in writing, and they had to collect many vocabularies, so that they can easily write a story. After some students read their story in front of the class, teacher hope the student they would not difficult making narrative story because they learned writing narrative text by using different song from the first and second meeting. The teacher asked the students about the problem which they got in the previous meeting. The Finding of the Students’ Task Content was an important component in a composition.In narrative text, content was described the main idea of each paragraph. A good narrative text must have a good content. Good content contained supporting details and relevant topic (Joy, 1993:236).The result showed that in the first students’ task, none of the students got very good criterion. Most of them or 20 students got the poor criteria, 10 students got fair criteria, and 6 students got good criteria. It did not means that they could not write, but the way they expressed their ideas and all the information they got were not right. They still got confuse and they did not have many vocabularies to write so that it affected to their writing which were not easily understood by the reader. In the second students’ task, 5 student got very good criteria, but the amount of the students who got good criteria were increased. There were 14 students who got good criteria, 8 students got fair criteria, and 10 students got poor criteria. Even though the first task was not better than the second task , on the second observation the students could write easily and got no difficult about the grammar or vocabularies. One of the factor, the song was easy listening and the song had a good story which could be understood by the students. The organization of the text dealt with the generic structure of the text.In the narrative text, the generic structure consists of three parts, they were orientation, complication and resolution.Based on the table above, there were several result which described students’ ability in writing in term of organization. In the first task, 4 students got very good criteria, 7 students got good criteria, 17 students got fair criteria, and 8 students got poor criteria. In the first meeting, most of the students felt confused to write the text in line with the generic structure, they still got difficulty to present the story into the text. In the second task, there were 7 students got very good criteria, 15 students got good criteria, 14 students got fair criteria and 1 student got poor criteria. In the second meeting, the teacher tried to explain one more time about the generic structure before playing the song just in case to remind the students. That factor gave a positive effect, it can be seen from the second task which got better, though, there was 1 student got poor criteria, at least most of them were ready to understand how to write the narrative text. Vocabulary is a mastery of a composition which related to the mastery of effective words or idioms choice and usage. From the table above, it could be seen that in the first students’ task 3 students got very good criterion. Meanwhile, in the second students’ task, there were 9 students got very good criterion. It means that the combination of words that they used was good. They also good in word choice and usage. Then, there were 7 students got good criterion in the first students’ task. In the second students’ task, the students who got this criterion were 10 students. They made occasional error of word, choice and usage, but the meaning was still understandable. The students chose the correct words to build the sentences. The students who got fair criterion in the first students’ task were 20 students and it reduced to 15 students in the second students’ task. The students did frequent errors of word choice and usage, inappropriate register used of pararell structure. For the poor criterion, in the first students’ task there were 6 students, but in the second students’ task, the number was reduced into 2 students. Language use referred to the use of grammar, tense, number, word order/function, effective complex construction, articles, and pronouns. In narrative text usually used simple past tense, action verbs, saying verbs, and thinking verbs. According to the table, there were 2 students who got very good criterion in the first students’ task, and it increased into 10 students in the second students’ task. The students got few errors in using tense, word order/function, pronouns, and preposition. For the good criterion, there were 9 students who got it in the first students’ task and the number increased into 16 students in the second students’ task. It means that they made several errors in using tenses, word order/function, pronouns, and time signals. Furthermore, the students who got fair criterion were 11 students in the first students’ task, but the amount decreased into 7 students in the second students’ task. It means the students did frequent errors in using tenses, word order/function, pronouns, preposition, and time signals. For the pooor criterion, there were 14 students who got it. Fortunately, the number of the students decreased in the second students’ task into 4 students. The last component here was mechanics. Mechanics dealt with spelling, punctuation, capitalization, and paragraphing.Based on the table, 3 students got very good criterion in the first students’ task and 8 students got it in the second students’ task. The students did few errors of spelling, punctuation and capitalization. Next, there were 10 students who got good criterion in the first students’ task and the number increased into 17 students in the second students’ task. 16 students got fair criterion in the first students’ task and it number decreased into 9 students who got it. Meanwhile, for the poor criterion there were 7 students in the first students’ task and decreased into 3 students in the second students’ task. The most common error found when the students wrote thedirect and indirect speech in the narrative text. DISCUSSION The Discussion of the Observation In this part, the researcher discussed the result of the observation to know the implementation of song to teach writing narrative text to the eleventh graders in SMAN 17 Surabaya. It also discussed the result of students’ writing after the teacher aplied the song to teach narrative text. The observation was conducted on 20th of March, 25th of March, and 27th of March 2014, which song was used or implemented as an media to teach narrative text. In this study, the students determined to write a story after the teachealied the song in their own words. Based on two meetings, the researcher could conclude that the activity was successful.The result of the observation was taken from the observation checklist and field note. It was obvious that the implementation of song to teach writing narrative text was based on the theory by Harmer (2004). Furthermore, there were three activities which had been conducted in implementing this research; pre-activity, whilst activity (pre-writing, whilst writing, post writing), and post activity. In every meeting, the teacher started the class by greeting the students and checking the attendance list. Then, it continued by reviewing lesson in the last meeting and introducing the new lesson that they would learn that day. In that moment, the students were enthusiastic and felt happy to hear that. According to Harmer (2007) explains that music and song could give different atmosphere in the classroom, it can amuse and entertain the learners. Moreover, after the teacher explained the objective of the lesson that day, she also gave brainstorming which asked the students about generic structer and language feature of narrative text. After the teacher explained a little about narrative text, she prepared the material, such as the leptop, LCD, and sound. It made the students’ happy and builtt the motivation in learning process. Before the teacher played the song, she gave a lyric which incomplete, then the teacher played the song three time. It was suitable with the theory from Brown (2013) which stated that students would be interested in learning language through song. Song could motivate the students in getting ideas of stories to write. In every meeting, there were three activities which had done by the teacher. They were pre-activity, whilst activity, and post activity. In pre- activity, the teacher reviewed about narrative text to the student. She gave the generic structure, language feature and the example of narrative text to the students so that they remembered narrative text. Because of the teacher’s explanation, the students were able to remember all the things about narrative text.In whilst activity, the teacher gave an incomplete lyric to the students and asked them to read three minutes to read it. After that the teacher played the song three times. She asked the students to listen to the song carefully, so that the students could fill the blank lyric. After listening the song, discussed the story of the song. The teacher gave question to the student what the song about. Then, the teacher asked the students’ to write a narrative text based on points of narrative text that she had explained The last was post activity. In post activity, the teacher asked the students to submit their writing. Then, they were discussing the problem which they got during the writing activity. After thet, the teacher gave information what would they did in the next meeting. The teacher would give feedback the students’ writing in the next meeting.For the second meeting, the teacher did the same activity as the first meeting. She reviewed the lesson in last meeting. After the teacher explained what they would do that day, the teacher prepared the material. She gave text about lyric of another song which was incomplete. And then the teacher played the song three times. After playing the song, they discussed about what song about. After that, the teacher asked the students making narrative story in their own words. After the students making the story, the teacher asked them to submit the students’ work, and the teacher would give feedback to their writing. On the third observation, the teacher did not play the song anymore. She just gave the student’s writing and informed who had the best score. And the teacher asked the students who had the best score to read aloud about her story in front of the class. After the students read her story in front of the class, then the teacher gave feedback. Actually, in her lesson plan, on the third observation the teacher still had to apply the song to teach narrative, but she said that implemented the song twice was enough for students. Because it would make them did not get focuss to the lesson, and they would enjoy singing than enjoy learning the narrative text. So, on the third observation, theteacher did not aplay the song to teach narrative text. There was one different in teacher’s implementation from Harmer’s technique, it was giving an incomplete lyric to the students. In Harmer’s technique, the teacher gave lyric of the song to the students before playing the song, but in this observation, the teacher gave an incomplete lyric to the students, she asked the students to read about three minutes the lyric, after that the teacher played the song three times, and asked the students to listen carefully that song, so the students could fill the blank sentence. In this observation, the researcher saw that the implementation of song to teach writing narrative text did not appropriate with the theory. Because in chapter 1, process of writing were inventing, planning, drafting, revising and editing. And the teacher did not use those five components in process of writing. The teacher just played thje song and than asked the students to fill the blank sentence, after that they analyzed what the song about and the last the teacher asked the students to make narrative with their own words. The teacher used the result of the students’ writing task as the assessment. It had a purpose to know how the result of the students’ writing of SMAN 17 Surabaya after the teacher aplied the song to teach writing narrative text to the eleventh graders. In assessing the students’ writing task, the teacher used the ESL Composition Profile. The result of the writing tasks showed that in each meeting, the score of the students’ were getting better. Finally, it can be concluded that, implementation of song made the students easily to write a narrative story. The Discussion of the Students’ Task The total of the students’ task that submitted to the teacher was different, in the first meeting, the total task was 36 tasks and in the second meeting, the total task was 37 students. It happened because in the first meeting, there were one student who did not join the class and in the second meeting there was no absent.The data from the task was taken in the first and second meeting. The results of the students were totally different, because the songs were different. From the first to the second work, the students’ work was different. The students’ work in the second meeting was better than the students’ work in the first meeting. In the term of content, no students got good mark in the first meeting, but it increased in the second meeting. It happened because the students got confused what story they would write. They had not prepared the story yet. In the term of organization, the result of the first meeting was not too bad, because there were four students who got very good criterion, but eight students got poor criterion. In the second meeting fifteen students got good criterion. Actually, most of them understood about the organization which related to the generic structure, but they still made a few mistakes to write it. In term of vocabulary, the result in the first meeting mostly dominated by the students who got fair criterion. Mostly, the level of the students in the term of vocabulary was average. In the first meeting, the vocabulary in the composition of some students were limited, but in the second meeting, the vocabulary of the composition more than before. In the term of grammar or language use, the students seemed to have no difficulties, but still some mistakes were made by them in using the tenses. Fortunately, the students’ task in term of grammar in the first meeting better than those in the second meeting . The poor criterion was always made by the same person. In the term of mechanics, the researcher could conclude that most of the students were good in mechanics. They really paid attention to the capitalization, punctuation and spelling. Even though, there wassevent students who got poor in the first meeting, most of the students got good criterion in the second meeting. From the explanation above, it can be concluded that there were many students who were able to write narrative story composition with correct generic structure of narrative text, grammar, vocabulary, and mechanic, but they had to pay more attention to content. The difficulty appeared because the students got confuse what story they would write, because they had no idea to write the story. The complete data can be seen on appendix. CONCLUSION AND SUGGESTION Conclusion The researcher concludes that the implementation of song had been done well by the teacher. The teacher also got success to motivate the students to be more active in the process of teaching and learning.Based on the data for answering second research question, the result of students’ work was satisfaction. From five elements, only in term of content that none of the students got very good criterion in the first meeting, but for other aspects, there were some students who got very good criterion. Suggestion The first suggestion, it is a must for the teacher to be more creative in teaching and try to figure out other media in the learning process. The media can be inform of picture, video, and music. It can help the students learn the target language easily and at the same time it will reduce their restlessness and boredom.And the second, the teacher should rearrange again the the lesson plan of the activity because the time is limited to conduct the writing activity.And the last, when the teacher was looking around, the students compete to get the teacher’s attention. So the teacher should make them to be patient and do not make a noise. REFERENCES Arikunto, Suharsimi. 2006. Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta. Rineka Cipta. Brown, H.D. 2003. Language Assessment: Principles and Classroom practices. Fransisco State University. Longman. Harmer, J. (2004). How to Teach Writing. England. Pearson Longman. Harmer, J. (2007). The Practice of English Language Teaching. Fourth Edition. England. Pearson Longman. Hancock, M. 2001. Using Song and Games in the Language Classroom. Lado, R. 1964. Language Teaching: A Scientific Approach. New York: McGraw-Hill, inc. Lo, Li Fai. Developing Second Language Skills: Theory to Practice. US: Houghton Miffin Company. Murphey, Team. 1992. Music and Song. London. Oxford University Perss. Nunan, David. 2003. Second Language Teaching and Learning. New York: International Thompson Publishing Company. Robert, Edgar. Literature An Introduction to Reading and Writing. New Jersey: Englewood Cliffs. 1998.